2017
DOI: 10.4049/jimmunol.1700380
|View full text |Cite
|
Sign up to set email alerts
|

T Cell–Derived CD70 Delivers an Immune Checkpoint Function in Inflammatory T Cell Responses

Abstract: The CD27–CD70 pathway is known to provide a costimulatory signal with CD70 expressed on antigen-presenting cells while CD27 functioning on T cells. Although CD70 is also expressed on activated T cells, it remains unclear how T cell-derived CD70 affects T cell function. Therefore, we have assessed the role of T cell-derived CD70 using adoptive transfer models including autoimmune inflammatory bowel disease (IBD) and allogeneic graft-versus-host disease (GVHD). Compared with WT T cells, CD70−/− T cells surprisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 40 publications
2
25
0
Order By: Relevance
“…However, during transient infections, CD70-driven co-stimulation enhances T cell immune responses without resulting in T cell exhaustion 79 , 80 . In line with these data, O’Neill et al have described a role for T cell-derived CD70 co-stimulation restraining inflammatory T cell responses by inducing T cell apoptosis in mouse models of autoimmune inflammatory bowel disease (IBD) and GvHD 81 . Here, we have shown that CD70 is expressed by Tregs following activation and that CD70 + Tregs (stably expressing CD70) after prolonged in vitro stimulation, can provide sufficient co-stimulation to induce T cell activation and proliferation.…”
Section: Discussionmentioning
confidence: 84%
“…However, during transient infections, CD70-driven co-stimulation enhances T cell immune responses without resulting in T cell exhaustion 79 , 80 . In line with these data, O’Neill et al have described a role for T cell-derived CD70 co-stimulation restraining inflammatory T cell responses by inducing T cell apoptosis in mouse models of autoimmune inflammatory bowel disease (IBD) and GvHD 81 . Here, we have shown that CD70 is expressed by Tregs following activation and that CD70 + Tregs (stably expressing CD70) after prolonged in vitro stimulation, can provide sufficient co-stimulation to induce T cell activation and proliferation.…”
Section: Discussionmentioning
confidence: 84%
“…These data suggest the maximal engagement of cDC1s with TLR3/CD40 stimulation for the development of more effective neoantigen vaccine therapy, and the potential implications of CX3CR1 as a circulating T-cell predictive biomarker for response in future clinical studies. background have been previously described (60). For inducible Cd2-cre/Cx3cr1+/DTR mice, we crossed CD2-Cre mice with CX3CR1-DTR mice to generate Cd2-cre/Cx3cr1+/DTR mice, allowing induction of DTR in CX3CR1+ CD8+ T cells.…”
Section: Discussionmentioning
confidence: 99%
“…CD27 + and CD70 + cells often secrete higher levels of IFNɣ and are therefore more effective at inhibiting viral replication [220]. This is in contrast to studies looking at CD27 in the context of strong and persistent immune challenges, such as chronic infections or GVHD, where CD27-CD70 have been shown to play an inhibitory role on T cell responses [216,[223][224][225]. The role of CD27 in diseases is also dependent on tissue context and duration of expression [22].…”
Section: Cd27 and Cd70mentioning
confidence: 99%